Code-switching in French-language mathematics classes: practices and motivations. (مجلة إحالات, 2026)
The present study aims to explore the use of the first language in a context ofteaching DNL (non-linguistic subject) in French as a foreign language. Three mathematics class interactions of the secondary school will be examined. The data will be collected by audio recording, three sequences for each of the three classes, a questionnaire will be distributed to students and a teacher interviews. This aims to highlight the use of codeswitching in the DNL in French and the motivations to resort to Arabic in interactions ratherthan the target language.